Pengembangan Media Kubus Bergambar untuk Meningkatkan Kemampuan Membaca Siswa Kelas II Sekolah Dasar - Tarni Tarni; Suharno Suharno; Sri Tatminingsih (Universitas Mathla'ul Anwar Banten, 2022)
The purpose of this research is to describe the development of pictorial cube media and to describe the effectiveness of pictorial cube media. This study uses the Research and Development (R&D) model. Data collection techniques with tests, non-tests, and interviews. The results showed that the validity of the illustrated cube learning media by media expert validators was 88.75 (very feasible) and 90.67 (very feasible) for language eligibility. The effectiveness of the illustrated cube media as measured by the before-after experimental design is known that the average value before using the media is smaller than the average value after using the media, thus the media developed is effective to be used as a medium for learning Indonesian. The value of F standard gain = 3.101 with a significance level of 0.088, this proves that the value variance between the experimental class group 1 and the experimental class group 2 is homogeneous. The standard gain t value for the same variance is (-5.497) which is greater than the ttable value of 0.05, the t value for df = 30 is 1.697. The results show that the value of tcount > ttable is tcount = (-5.497) > ttable 0.05 = 1.697. Thus, it can be concluded that there is a significant (significant) difference between the pretest and posttest scores in Indonesian language learning, this means that pictorial cube media can improve the second grade students' understanding of the basic Indonesian language lessons. 3.3. Determine vocabulary and concepts about the geographical environment, economic, social, and cultural life in the surrounding environment in Indonesian or regional languages ​​through written, oral, visual and/or environmental exploration texts.